(untitled) (Revista Apotheke, 2022)
This article has the purpose to show the possibilities of some transformative experiences on environmental education by the subject of science and art aming the formation of educators and researchers. Trought critical reflection on the production of knowledge directly over reality, it contributes to reinforce the thought over the complex network that is developed in our educational activity spaces- places among different actors- state, academia, industry, non- governmental institutions, communities, local leaders and the collective subjects-simultaneously productors of life and its knowledge. Understanding this web involves alternating experiences on conducting activities in between diferent cultural spaces as UERJ and Mangueira community, in Rio de Janeiro , Brasil. Mixing university and community, we experience non- hierarchized knowledge and sensibilities conjunction.